Peran Technology Readiness, Job Meaningfulness, dan Work Engagement dalam Adaptive Performance - Nur Efa Rista; Andri Kusmayadi (CV Edujavare Publishing, 2024)
This study examines the influence of factors such as technology readiness, job meaningfulness, and work engagement on employee adaptation to digital work changes at Hermina Hospital. The population is 150 non-medical employees, and data collection is done through an online survey with Likert scale. The results show that technology readiness does not have a direct effect on adaptive performance, but has a positive effect on job meaningfulness. Job meaningfulness also acts as a mediator between technology readiness and adaptive performance. In addition, work engagement positively affects adaptive performance and moderates the relationship between technology readiness and adaptive performance. This research provides important insights in the context of adaptation to changes in digital work in hospitals.